(untitled) (Research, Society and Development, 2023)
Objectives: This study aimed to evaluate the quality of life (QoL) of patients undergoing scalp cooling during chemotherapy and to describe hair density data assessed by trichoscopy. Background: Hair loss during chemotherapy is a common and distressing side effect, and prevention can be done through scalp hypothermia. Methods: A prospective cohort study was conducted at a single oncology center in Brazil. Patients undergoing scalp cooling during chemotherapy were included. QoL and body image satisfaction (BIS) questionnaires were administered at the beginning and end of treatment. Data on alopecia were collected. Trichoscopy with a Fotofinder® device was performed at the beginning, before the second cycle, and at the end of treatment. STROBE guidelines were followed for the development of this study. Results: Twenty-seven patients were included. There was no difference in mean QoL or BIS scores in the comparison of patients with hair loss < 50% with those with hair loss ≥ 50%. Better outcomes in the QoL and BIS scales were found in patients treated with anthracyclines. Hair density described by trichoscopy showed a maximum reduction of up to 16.3%, and loss was more common in the frontal area. Conclusions: Thus, there is no clear evidence of better QoL in patients with a lower grade of alopecia after scalp cooling during chemotherapy. Validated scales can be useful for assessing QoL in this population.